Analisis Spasial Terhadap Kesesuaian Lahan Permukiman Pada Kawasan Rawan Erupsi Gunung Agung Pada Kawasan Permukiman Kecamatan Rendang, Karangsem - Anggreni, Ni Luh Jaya; Putri, Putu Indah Dianti (Jurnal Ilmiah Poli Rekayasa, 2024)
Mount Agung is a type of volcano that is still active and showing signs of eruption. The existence of Mount Agung is located in Rendang District, Karangasem Regency, and is a tourist attraction for the area, which encourages the acceleration of development, so that quite a few people in Rendang District, or indeed, the existing ones, live in residential areas that are included in areas prone to volcanic eruptions. This will, of course, be high-risk because the living conditions are unsafe against the risk of a disaster that could come suddenly. To anticipate the possibility of being affected by volcanic eruptions, research is needed to identify the level of vulnerability to Mount Agung eruptions in residential areas of Rendang District. The research method used is a quantitative descriptive method using a spatial analysis approach with the help of GIS (Geographic Information System) analysis tools and scoring analysis. Based on the results of the analysis, it was found that residential areas in Penempatan, Besakih, and Menanga Villages are not suitable for housing because they have a high level of risk of volcanic eruptions with a total score of 131. Residential areas in Rendang, Nongan, and Pesaban Villages are categorized as suitable for housing because they have a low risk of volcanic eruptions, with a total score of 126. It can be concluded that residential areas in the villages of Penempatan, Besakih, and Menanga have a high risk of being affected by volcanic eruptions. so that in the future it is hoped that it will become a reference for the area when there will be a relocation or when developing built-up land so that the risk of disasters in this area can be anticipated.